SAT0447 MANAGEMENT OF GOUT: AN AUDIT IN PRIMARY CARE GENERAL PRACTICE IN LEICESTERSHIRE, UNITED KINGDOM. (June 2019) - Aboo, Ahmed; Goodyer, Larry; Lakhani, Neena; Hadi, Muhammed; Sunmboye, Kehinde
Abstract : Background: Both acute and long-term management of gout in primary care in UK is reportedly suboptimal 1, with patients rarely being offered lifestyle advice or urate Lowering Therapy (ULT). Further, ULT is often not titrated according to the patient's serum uric acid (sUA) levels, so that they fail to achieve target sUA levels. Objectives: To audit and evaluate the management of gout in patients in a primary care setting against the current guidelines treat to target guidelines set by the British Society of Rheumatology (BSR) 2 . Methods: Audit criteria were derived from the latest BSR gout guideline (Hui et al; 2017). A randomised sample of adult patients with a read code for the diagnosis of gout from Jan 2006-Jan 2018 was chosen from six large general practices in Leicestershire County of the United Kingdom. The data collected included demographics, provision of patient information, management of acute attacks and prophylactic treatment, screening of appropriate co-morbidities, dosing of urate-lowering therapy (ULT) and titration of doses against measurement of uric acid levels. Results: Data was obtained for 861 patients The mean age was 60 years and 91% were male, 21.5% were recorded as being provided with written information about gout and 60.5% of patients were treated with NSAIDs and COXIBs for acute attacks of gout. When colchicine was prescribed to patients, 71% had no dose recorded in their clinical records. 323 (37.5%) of patients were prescribed a ULT and the recorded starting dose of allopurinol was 100mg daily for 73.8%. Titration of subsequent allopurinol doses was recorded in only 21% of patients. 539 patients (62.6%) had no record of a serum urate level check after starting ULT. Conclusion: Clinical records indicate that the management of gout by UK General Practitioners in Primary Care is suboptimal in concordance with the BSR guidelines. It was clear that general practices did not employ the treat to target strategy. There is a clear need for increased GP awareness and adherence to the BSR guidelines in order to optimise deficient areas of care, particularly in patient education, initiation and titration of ULT and monitoring of serum urate levels in gout patients. Appropriate patient recording templates are needed so that key information is captured during a patient consultation in order to enable medicines optimisation for those with gout. Most aspects of gout management in primary care did not concord well with published BSR guidelines. References: [1] Kuo, C., Grainge, M.J., Mallen, C., Zhang, W. and Doherty, M. (2014) Rising burden of gout in the UK but continuing suboptimal management: a nationwide population study. Annals of the Rheumatic Diseases, [online] 74(4) pp.661-667. [2] Hui, M., Carr, A., Cameron, S., Davenport, G., Doherty, M., Forrester, H., Jenkins, W., Jordan, K., Mallen, C., Mcdonald, T., Nuki, G., Pywell, A., Zhang, W. and Roddy, E. (2017) The British Society for Rheumatology Guideline for the Management of Gout. Rheumatology, [online] 56 (7) pp. e1-e20. Disclosure of Interests: None declared